'These people protesting might not be so strident if their own jobs were on the line': Representations of the 'economic consequences' of opposition to the Iraq war in the Irish national press. (August 2016) - Coulter, Colin; Browne, Harry; Flynn, Roddy; Hetherington, Vanessa; Titley, Gavan
In this article, the authors examine the ways in which the social movement in Ireland opposed to the Iraq war was represented in the national press. The article draws upon data generated by the largest research project of its type ever conducted in an Irish context. The authors considered representations of the anti-war movement in 11 daily and Sunday newspapers over a period of 9 months. One of the principal threads that ran through newspaper coverage of the time centred upon concerns about the possible 'economic consequences' of opposing the war against Iraq. A close reading of the data reveals that the familiar reliance of journalists on official sources and interpretations ensured that the national press tended to cast the anti-war movement in Ireland as a danger to both the regional and national economy at a time of seemingly unprecedented prosperity.